2021
DOI: 10.1049/cvi2.12023
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical bilinear convolutional neural network for image classification

Abstract: Image classification is one of the mainstream tasks of computer vision. However, the most existing methods use labels of the same granularity level for training. This leads to ignoring the hierarchy that may help to differentiate different visual objects better. Embedding hierarchical information into the convolutional neural networks (CNNs) can effectively regulate the semantic space and thus reduce the ambiguity of prediction. To this end, a multi-task learning framework, named as Hierarchical Bilinear Convo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Zhang et al [36] developed Hierarchical Bilinear CNN model by combining convolutional networks with multitask learning on the hierarchical visual structures. Hierarchical bilinear CNN utilized VGG16 for constructing a network of inner output branches.…”
Section: Deep Learning Based Image Classification Modelsmentioning
confidence: 99%
“…Zhang et al [36] developed Hierarchical Bilinear CNN model by combining convolutional networks with multitask learning on the hierarchical visual structures. Hierarchical bilinear CNN utilized VGG16 for constructing a network of inner output branches.…”
Section: Deep Learning Based Image Classification Modelsmentioning
confidence: 99%
“…To that moment, branches were treated independently, but authors such as Inoue et al [16] and Zhang et al [17] demonstrated the benefit of interconnecting branches. Indeed, they showed that branches can complement information from different hierarchy levels during training.…”
Section: Related Workmentioning
confidence: 99%
“…In [16], branches are connected similary to [17], but instead of connecting the representation extracted from the central block, they connect the pre-softmax layer y…”
Section: A Branched Architecturementioning
confidence: 99%
See 2 more Smart Citations